Sociodemographic and Health Profile of Heterosexual Men Living With HIV in Ontario, Canada. (July 2017) - Wheeler, Kristen M.; Antoniou, Tony; Gardner, Sandra; Light, Lucia; Grewal, Ramandip; Globerman, Jason; Husbands, Winston; Burchell, Ann N.; ,
In Ontario, Canada, the number of heterosexual men living with HIV has increased over time, yet they remain an understudied population. The study objective was to describe the sociodemographic and clinical characteristics of this population, using data from a multisite clinical cohort of patients receiving HIV care. Sociodemographic and clinical characteristics of men interviewed between 2010 and 2012 were compared according to their self-identified sexual orientation, followed by multivariable linear and logistic regression to assess the association of sexual orientation with CD4 cell count, viral load, hepatitis C co-infection, self-rated health, and mental health concerns after adjustment for covariates. A total of 552 men identified as heterosexual, 2, 023 as gay, and 171 as bisexual. Compared to gay and bisexual men, heterosexual men were more likely to have been born outside of Canada (34.8%); more likely to report African, Caribbean, or Black ethnicity (26.4%) or Indigenous ethnicity (13.6%); and more likely to have low socioeconomic status (59.5% earning less than 20, 000 per year), and/or a history of injection drug use (31.7%). Relative to gay men, heterosexual men had 5.19 times the odds of co-infection with hepatitis C virus regardless of injection drug use history (95% confidence interval = 3.87-6.96), and 40% lower odds of rating their health as excellent or good (95% confidence interval = 0.50-0.84). HIV-positive heterosexual men in Ontario constituted a socially marginalized group characterized by a high prevalence of injection drug use history and hepatitis C co-infection.